AUGMENTATION OF FERTILITY IN POSTPARTUM ANESTRUS COWS - TRIPATHY, A K; MOHANTY, D N; DAS, S; MISHRA, P C (The Indian Journal of Animal Reproduction, 2011)
The _main objective of the study was to augment fertility in postpartum anestrus cows by application ofProgesterone therapy alone or in combination with Estrogen through parentral (i/m) route. Thirty postpartumanestrus cows allotted to three equal groups were administered intramuscularly progester6ne 500 mg (P- Depot)and estradiol valerate 10 mg (Progynon- depot) on day "0" followed by P-Depot on 7th day (Group I n-10). TheGroup II (n-1 0)received P-Depot on day "O" followed by Progesterone and estrogen therapy on day 7. But Group Ill(n-10) cows were given only progesterone on corresponding days. Serum P4 concentration was significantlyhigher (P
Keywords: Post partum Anestrus; Estradiol valerate; P-Depot; Conception rate